Changes in the fluorescence excitation and emissions spectra of heated and frying rapeseed oil and sunflower oil - Szukay, Beata; Stachura, Wojciech; Saletnik, Łukasz; Budzyński, Jacek; Szymańska, Justyna; Fisz, Jacek (Wydawnictwo Politechniki Łódzkiej, 2019)
Frying is a popular method of cooking (meals preparation). Heating and deep-fat frying cause a series of chemical reactions, such as oxidation of polyunsaturated fatty acids and vitamin E, as well as formation of trans isomers and products of peroxidation. These chemical reactions cause organoleptic and nutritional changes in the product, which may have a negative effect on health. For this reason, the usefulness of many methods for evaluation of refined oils quality is investigated. The fluorescence spectroscopy is increasingly used for this purpose. The aim of the study was to monitor the changes in emission and excitation spectra of refined rapeseed oil and sunflower oil after processes of heating and frying frozen French fries. The obtained results show the differences between the shapes of fluorescence excitation and emission spectra of both oils due to the two processes and these changes depend on duration of both processes. This study indicates that fluorescence spectroscopy is a promising method for evaluation of changes in oils during heating or frying.
Keywords: fluorescence spectroscopy; vegetable oils; deep frying; spektroskopia fluorescencyjna; oleje roślinne; smażenie zanurzeniowe; smażenie na głębokim oleju